LEGAL REASONING DISSENTING OPINION HAKIM DALAM PENERAPAN PASAL 2 AYAT 1 UU TPPO PADA PROSTITUSI ANAK - Desy Ervitasari; Riri Tri Mayasari (University Of Bengkulu Law Journal, 2025)
This research examines the disparities in legal reasoning within the Manna District Court Decision Number 00/Pid.Sus/2025/PN Mna regarding the application of Article 2, Paragraph 1 of the Law on the Eradication of the Crime of Trafficking in Persons (TIP Law) in cases of child prostitution. The central legal issue lies in the conflicting interpretations of the elements of "recruitment/receipt," "vulnerable position," and "child consent" in determining the existence of sexual exploitation. This study aims to analyze the arguments presented in the dissenting opinion that rejected the application of Article 2, Paragraph 1 of the TIP Law and to evaluate their alignment with legal norms and child protection objectives. This is a normative legal research employing statutory, conceptual, and case study approaches. The findings indicate that the majority of the judicial panel adopted a child protection approach based on the lex specialis principle, emphasizing that the victim's status as a child constitutes a vulnerable position that cannot be waived by consent; thus, the element of exploitation is deemed fulfilled. Conversely, the dissenting opinion positioned coercion or power relations as the primary indicators of trafficking and tended to qualify the act as a general crime against morality (decency). This study concludes that these disparities underscore the necessity for consistent interpretation of "vulnerable position" and "child consent" to ensure that the application of the TIP Law is not narrowed down to mere general moral offenses.